The Effectiveness of the Functional Training for Pharmacy and Food Junior Expert Supervisors during Pandemic with Blended Learning Methods - Eryani, Yulia; Azizi, Khiratul; Ningsih, Listia (Jurnal Borneo Administrator, 2022)
The Functional Training for Pharmacy and Food Junior Expert Supervisors has been conducted since 2019 with classical face-to-face method (offline). In early 2020, the method was replaced with blended learning methods using asynchronous and synchronous modes. The Covid-19 Pandemic requires the synchronous approach, initially conducted offline face-to-face with the participants, to replace online meetings using a video meeting application. This study aims to analyze the effectiveness of the functional training for pharmacy and food junior expert supervisors with the blended learning method. This research performed a quantitative parametric method using the Mann-Whitney test method. The number of offline training respondents was 59 people, and online training (blended learning) respondents were 753 people. The variable used to measure the effectiveness was the training evaluation. The study results indicated that the online activity of the Pharmacy and Food Junior Expert Supervisors was more effective than the offline training. This result was proved by The Mann-Whitney test method using SPSS. The evaluation result before the Covid-19 Pandemic with the classical method was significantly different from Blended learning during the Covid -19 pandemic, which was more effective. In this study, researchers also employed SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to explore essential aspects for continuing this training. Thus, the blended learning method is effective and continues using an online video meeting application